Structural and electronic properties of graphene nanoflakes on Au(111) and Ag(111) - Tesch, Julia (Nature Publishing Group, 2016)
We investigate the electronic properties of graphene nanoflakes on Ag(111) and Au(111) surfaces by means of scanning tunneling microscopy and spectroscopy as well as density functional theory calculations. Quasiparticle interference mapping allows for the clear distinction of substrate-derived contributions in scattering and those originating from graphene nanoflakes. Our analysis shows that the parabolic dispersion of Au(111) and Ag(111) surface states remains unchanged with the band minimum shifted to higher energies for the regions of the metal surface covered by graphene, reflecting a rather weak interaction between graphene and the metal surface. The analysis of graphene-related scattering on single nanoflakes yields a linear dispersion relation E(k), with a slight p-doping for graphene/Au(111) and a larger n-doping for graphene/Ag(111). The obtained experimental data (doping level, band dispersions around EF, and Fermi velocity) are very well reproduced within DFT-D2/D3 approaches, which provide a detailed insight into the site-specific interaction between graphene and the underlying substrate.